Peran Kredibilitas Influencer, Iklan, Citra Merek dalam Memengaruhi Keputusan Pembelian Produk Skincare di TikTok Shop - Kamila, Vera Rindiani; Hariyadi, Guruh Taufan; Nuryanto, Imam; Putra, Febrianur Ibnu Fitroh Sukono (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of Influencer Credibility, Advertising, and Brand Image on Purchasing Decisions for skincare products on TikTok Shop. A quantitative approach was used with a survey method of 139 respondents who are TikTok Shop users and have purchased skincare products. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results of the analysis show that Influencer Credibility and Brand Image have a positive and significant influence on Purchasing Decisions. Conversely, Advertising does not have a significant influence on Purchasing Decisions. These findings indicate that trust in influencers and positive perceptions of brands have a more dominant role in driving purchasing decisions than advertising. This study provides implications for business actors to optimize digital marketing strategies by emphasizing influencer credibility and strengthening brand image.